Illustration / For Professional Communicators - Squires Vicky (Batsford, 1993)
What is the Purpose of Your Illustration, Who is it For, For How Long Will it Be Seen, How Will It Reproduced, How Much Time Has Been Allowed, What are Your Own Particular Skills, Glossary, Bibliography, Index.
What is the Purpose of Your Illustration, Who is it For, For How Long Will it Be Seen, How Will It Reproduced, How Much Time Has Been Allowed, What are Your Own Particular Skills, Glossary, Bibliography, Index.